(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2025)
This article analyzes the loss of personality rights of women in street situations, considering their social invisibility and the extreme marginalization they face. Indeed, based on the concept of structural underclass by Jessé Souza, it is evident that these women constitute the “underclass of the underclass,” as they are part of a group subjected to multiple forms of exclusion and violation of fundamental rights. In this context, the objective of this study is to investigate how the loss of personality rights affects these women, verifying the impacts of this situation and highlighting how the intersectionality between poverty and gender leads to a position of enormous vulnerability. Thus, based on bibliographic review and documentary analysis, it is demonstrated that the absence of housing, lack of access to health and hygiene, gender-based violence, and the lack of effective public policies are factors that perpetuate this condition. In addition, the role of the State, the Judiciary, and society in formulating measures to guarantee the dignity and protection of these women is discussed, highlighting initiatives such as the “National Policy for Decent Work and Citizenship for the Homeless Population” (PNTC PopRua) and the “National Judicial Policy for Attention to People in Street Situations” (PopRuaJud). It is concluded that the violation of the personality rights of women in street situations reflects maximum exclusion and total dehumanization, requiring effective public policies to guarantee their dignity and recognition as subjects of rights.